Bio-Green Foliar Spray Enhances Rice Growth and Productivity in Cambodia - Tak Tha; Ply Preap; Seyha Sorl; Pao Srean; Visalsok Touch (Badan Penerbitan Fakultas Pertanian (BPFP), 2021)
The use of bioproducts as biostimulants to stimulate plant growth and to increase yields as an alternative to chemical fertilizers are currently being promoted for cost-effective, sustainable and environmentally friendly agricultural practices of crop production systems. The objective of the study was to determine plant growth and productivity of rice responded to Bio Green application. A short growing period (90 – 95 days) OM-5451 rice variety was used in this study. The rice plants were cultivated in the randomized-completed block with two treatments and six replications in the plot of 2 m * 2 m. Di-ammonium phosphate (DAP) fertilizer was applied once at a rate of 100 kg/ha. For treatment, Bio-green with a solution of 1% (v/v) was weekly applied as foliage spray; and without Bio-Green as control. The results showed the grain yield was 3.7 t/ha in the treatment and 2.83 t/ha in the control, indicating that 36.4% of the grain yield was increased. The Bio-Green could be significantly used as plant biostimulants to promote plant growth and grain yield in rice in Cambodia.